Significant clinical features in pediatric pneumonia - Wisman Dalimunthe; Rini S Daulay; Ridwan M Daulay (Paediatrica Indonesiana, 2013)
Background Pneumonia is the leading cause of childhood mortalityin the world. Although WHO develops an algorithm fordiagnosing pneumonia, many clinicians still under or overdiagnosethis disease.Objective To assess associations of cough, tachypnea, fever, andchest indrawing with pneumonia in children.Methods This cross-sectional study was conducted using medicalrecords of children aged less than 5 year old with one or more clinicalsigns of pneumonia such as cough, fever, tachypnea, and chestindrawing in Haji Adam Malik Hospital, Medan from January2009 to December 2011. Pneumonia was diagnosed by pediatricrespirologists based on history-taking, and physical, laboratoryand radiology examinations. Patients with incomplete datawere excluded. Data was analyzed by bivariate and multivariateanalyses.Results Of 420 subjects, the majority were aged 3 to 23 monthsand there were more boys than girls. Clinical signs assessed forwere cough (82.9%), tachypnea (31 %), fever (79.3%), and chestindrawing (40.2%). Age < 24 months (OR 2.563; 95% CI 1.497to 4.387), cough (OR 2.274; 95% CI 1.042 to 4.960), tachypnea(OR 2.249; 95% CI 1.282 to 3.947), and chest indrawing (OR6.993; 95% CI 4.017 to 12.173) were significant predictors forpneumonia.Conclusion Age less than 24 months, cough, tachypnea, andchest indrawing are significantly associated with pneumonia.